HUBUNGAN RIWAYAT PENYAKIT INFEKSI DENGAN KEJADIAN STUNTING - hasim, rina; Aksohini Wijayanti, Tut Rayani (NHM PRESS, 2024)
Stunting is a lack of nutrients due to the accumulation of nutrients that Insufficient. The purpose of this study is to see if there is a historical relationship Infectious Diseases with Stunting Incidence in Puskesmas Jailolo. Design control cases with analytical survey methods and retrospective approaches. The population in this study was all toddlers from the Jailolo Health Center, with an age range of 24 to 59 months. Research Techniques It uses purposive sampling by sampling 41 cases and 41 controls. This research includes univariate and bivariate analysis, as well as tests only square. Statistical tests show a relationship between p-value 0.000 and OR 0.111 between the history of infectious diarrhoea disease and the incidence of stunting, and the relationship between p-value 0.023 and OR 5.484 between the history of ISPA infection and stunting incidence.